Local Government Use Website and Twitters as Communication and Interaction Tools - Misran Misran; Dede Kurnaedi; Achmad Nurmandi; Dian Eka Rahmawati; Budiman Budiman (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2021)
Website and Twitter Local Government is one government implementation to optimize public services to increase efficiency, effectiveness, transparency, and government administration accountability. This paper aims to determine the quality of all city governments' websites and Twitter in West Java province, Indonesia. The research method used is descriptive interpretive by using scoring analysis techniques, namely the author gives a score for each element of the site assessment indicator based on several theories to find the weight of the score and the quality level of the website, and uses the N Vivo 12 Plus application to assess the Twitter of the city government in the province of West Java. The results showed that of all city government websites in the province of West Java, there were 4 (four) quality websites, 4 (four) websites that were of sufficient quality, and 1 (one) website was less qualified, so that the overall city government website was overall, namely 44.44% of high quality, 44.44% of sufficient quality, and 11.11% of low rate with quality status occupied by the City Government of Bandung, Bogor, Cimahi, and Cirebon; In the assessment of Twitter activity as a medium of communication and interaction with city governments throughout West Java, every city government has made efforts to fulfill public information and communication facilities as well as electronic services via Twitter. However, the implementation is less than optimal. So it is always suggested to improve the innovation and creativity of website and twitter management, monitor and evaluate and survey community satisfaction regularly to enhance the quality of the Website and Twitter of the city government.